VEGF‐C improves regeneration and lymphatic reconnection of transplanted autologous lymph node fragments: An animal model for secondary lymphedema treatment. Issue 3 (17th November 2014) - Schindewolffs, Lia; Breves, Gerhard; Buettner, Manuela; Hadamitzky, Catarina; Pabst, Reinhard
Abstract Secondary lymphedema occurs after for example breast cancer surgery and radiation in 20–50% of the patients. Due to the poor outcomes of surgical treatments in the past, the therapy often remains symptomatic. However, avascular transplantation of autologous lymph node fragments (LN‐Tx) combined with postoperative injections of vascular endothelial growth factor‐C (VEGF‐C) emerges as a potential surgical therapy. In this study, adult rats underwent LN‐Tx to investigate the following parameters of VEGF‐C application: time point, location and dosage. Furthermore, the influences of VEGF‐C on lymphatic reconnection and transplant regeneration were analyzed. The reconnection was investigated using intradermally injected blue dye and the regeneration was evaluated histologically using hematoxylin‐eosin (H&E) staining and immunohistochemistry. The higher dosage enhanced the reconnection rates significantly and showed a statistical tendency of improving regeneration. An application on early postoperative days and the injection into the medial thigh improved the reconnection significantly. However, these variables did not affect the regeneration statistically. This study confirms that LN‐Tx combined with lymphatic growth factor VEGF‐C is a possible approach in the therapy of secondary lymphedema and shows the important role of VEGF‐C application parameters.